2016
DOI: 10.1155/2016/8690380
|View full text |Cite
|
Sign up to set email alerts
|

Texture Profile Analysis of Sliced Cheese in relation to Chemical Composition and Storage Temperature

Abstract: The quantitative relationships among chemical composition, storage temperature, and texture of cheese were not fully understood. In this study, the effects of composition and temperature on textural properties of eight common varieties of sliced cheese were examined. The textural properties of sliced cheeses, including firmness, cohesiveness, adhesiveness, springiness, chewiness, and resilience, were measured by texture profile analysis after storage at 4 and 25°C for 4 h. Multivariate logistic regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 26 publications
8
28
2
1
Order By: Relevance
“…Adhesiveness is the work needed to overcome attractive force between food and other surfaces [30], which, in sensory terms, known as the degree to which the sample sticks to your teeth as mastication progresses [31]. Higher adhesiveness value reported herein for P4 cheese was in accordance to results reported previously by Zheng et al (2016) who reported that adhesiveness values correlated negatively with protein content [26]. The lower protein content allowed cheeses to melt better and thus increase the adhesiveness.…”
Section: Effect Of Protein Content On Textural Properties Of Spreadabsupporting
confidence: 89%
See 3 more Smart Citations
“…Adhesiveness is the work needed to overcome attractive force between food and other surfaces [30], which, in sensory terms, known as the degree to which the sample sticks to your teeth as mastication progresses [31]. Higher adhesiveness value reported herein for P4 cheese was in accordance to results reported previously by Zheng et al (2016) who reported that adhesiveness values correlated negatively with protein content [26]. The lower protein content allowed cheeses to melt better and thus increase the adhesiveness.…”
Section: Effect Of Protein Content On Textural Properties Of Spreadabsupporting
confidence: 89%
“…Cheeses-containing gums such as carrageenan (S3), guar gum (S4) and xanthan gum (S6) or carboxymethyl cellulose (S5) had higher values (P ≤ 0.05) for springiness compared with the remaining cheeses. Similar results was reported for cheeses containing carrageenan and xanthan gums which were usually used to reduce the total solids content in cheese for cutting the cost and to maintain the springiness of the final cheese [26]. In general, values for springiness in different cheeses were in the order of cheese made with carboxymethyl cellulose > guar gum > carrageenan > xanthan gum > Dairy gel 161 > Hitex 555 > modified starch > native starch, respectively.…”
Section: Textural Attributessupporting
confidence: 81%
See 2 more Smart Citations
“…The cheese texture is among parameters of cheese physical qualities that influence consumers' acceptance. The cheese texture changed during storage, which was influenced by chemical composition, in particular fat in the dry matter and moisture in the nonfat substances (Zheng et al, 2016). Table 1 shows the effects of storage temperatures on cheese hardness.…”
Section: Cheese Texturementioning
confidence: 99%